A new concept for a gas proportional scintillation counter: the annular anode. (1st May 2022) - Silva, P.A.O.C.; Azevedo, C.D.R.; Fernandes, L.M.P.; dos Santos, J.M.F.; Monteiro, C.M.B.
Abstract: A new design of a Gas Proportional Scintillation Counter (GPSC) for X-ray spectrometry is presented and a proof of concept is demonstrated. The proposed design is much simpler, having only one electrode, the anode. In addition, this electrode has an annular shape with its axis aligned with the photosensor axis. Since the scintillation region is limited to a small region near the anode, the solid angle subtended by the photocathode is similar relative to any position in the scintillation region and the amount of scintillation reaching the photosensor is independent from the position where the radiation interaction occurs. Standard GPSCs with uniform electric field design have the scintillation region parallel to the photosensor active area resulting in a dependence of the amount of light collected by the photosensor on the axial distance of the radiation interaction due to solid angle effects. These effects impose limitations on the size of the detector radiation window relative to the photosensor active area. Therefore, the annular anode allows to obtain a GPSC design with a larger radiation window relative to the photosensor area. A first GPSC prototype with a 10-cm diameter annular anode placed at a distance of 4.4 cm from the photosensor has an energy resolution of 14% for anode voltages of 8 kV and, according to simulations, it can reach 11% for anode voltages of 12 kV. This is worse than the values of 8–9% obtained with a standard GPSC which, on the other hand, have a window-to-photosensor diameter ratio lower than 0.8. Simulations have shown that the main factor degrading the energy resolution in this new design is the low number of photons impinging the photosensor due to the low solid angle subtended by the photosensor relative to the electroluminescence region of the detector. A compromise has to be made between the anode-to-photosensor diameter ratio as well as between the anode-to-photosensor distance and the energy resolution that can be achieved with the annular anode design.